ENGLISH AT TOURISM INDUSTRY: A MATERIAL DEVELOPMENT TO SUPPORT TRADERS OF TRADITIONAL MARKET - Restu Arini; Eni Rohmawati; Lu’luil Maknun (JISOS: JURNAL ILMU SOSIAL, 2022)
Malioboro of Yogyakarta with its traditional market, Beringharjo, becomes an attraction to both domestic and foreign tourists that inevitably it supports the tourism industry and the small business enterprises in that area. An excellent service is a must including the ability to build communication in English with the tourists. The study focuses on developing an English mini book to help the traders in communication with foreigners during the business transactions. It applied a designed-based research and involved 25 traditional market traders as participants. The data was gained through observation, questionnaire, and interview. The findings showed the designed English mini book was acceptable based on evaluation given by the traders with five aspects of evaluation: linguistics features, language authenticity, English activities in business field, vocabulary enrichment, and the book appearance